2005
DOI: 10.1097/01.aids.0000188422.95162.b7
|View full text |Cite
|
Sign up to set email alerts
|

Protease mutation M89I/V is linked to therapy failure in patients infected with the HIV-1 non-B subtypes C, F or G

Abstract: The results of the present study show that M89I/V is associated with PI experience in subtypes C, F and G but not in subtype B. M89I/V should be considered a secondary PI mutation with an important effect on nelfinavir susceptibility in the presence of L90M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
49
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 17 publications
0
49
2
2
Order By: Relevance
“…Recent analyses suggest that non-B viruses can develop specific mutations that differ from those identified in subtype B under the same treatment pressure (1,20). For example, in CRF01_AE but not in subtype B viruses, V75M seems to be significantly associated with stavudine treatment (2) and, in subtype C but not in subtype B, V106M is a signature substitution of patients treated with efavirenz (4).…”
mentioning
confidence: 99%
“…Recent analyses suggest that non-B viruses can develop specific mutations that differ from those identified in subtype B under the same treatment pressure (1,20). For example, in CRF01_AE but not in subtype B viruses, V75M seems to be significantly associated with stavudine treatment (2) and, in subtype C but not in subtype B, V106M is a signature substitution of patients treated with efavirenz (4).…”
mentioning
confidence: 99%
“…L89M was observed in two PI-naïve children with no evidence of PIs resistance. This mutation is a naturally occurring polymorphic substitution which may lead to early development of drug resistance in some infected patients (Abecasis et al 2005;Sanches et al 2007). On the other hand, the L89I mutation was reported in two children who were receiving RTVregimen and presented multi-drug viral resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed novel mutations or differences in the prevalence of known mutations in non-B subtypes (1,3). Others have demonstrated the impact of the genetic background on subtype dependencies in drug susceptibility and resistance development (2, 6, 7).…”
mentioning
confidence: 99%